Teleologie und politische Vernunft Entwicklungslinien republikanischer Politik bei Aristoteles und Thomas von Aquin - Maier, Eva Maria (Nomos Verlagsgesellschaft mbH & Co. KG, 2002)
This book describes stages of development of the conception of an ideal republic that is fundamentally based on practical reason. It is widely understood that this conception is paradigmatically represented in the political thought of Aristotle and conveyed by its reception by Thomas Aquinas. This early concept of a liberal republic - which is in some ways certainly marked by the constraints of ancient philosophy on the whole, is even considered to have contributed to the development of the modern state and its instruments of political reason. Part 1 presents Aristotle's conception of "civil society" which is built upon man in his specific nature of humanity. From this point of view "political" government is intrinsically related to the mutual recognition of free and equal fellow citizens. Thus establishes a strict standard of criticism of any arbitrary or illegitimate presumption of political power. Nevertheless, Aristotle's "Republic" relies on limiting conditions of political subsistence as they arise from a specific ancient point of view that sets a clear limit to our modern expectation of freedom and equality. Above all, subjectivity, at least the perfection of virtuous citizenship, is supposed to be indispensably linked to a specific political, institutional and moral framework. This framework is derived from Aristotle's concept of "teleology", which pervades his whole philosophy. Therefore, Aristotle's approach shall be investigated in a most complex and comprehensive way in its close systematic link to all fields of philosophy, including practical reason, physics and metaphysics, in order to enable a most distinct historical judgement that will also finally reveal its actual significance. E.g. Aristotle's concept of teleology, though introduced by the investigation of "natural movement", is also applied to his ethics of practical reason. This does not imply, however, any dependence of law or politics on natural goals, but only reclaims a fundamental structural analogy between both, nature and habits, while adhering to their clear methodological separation. Part 2 is devoted to elaborate the systematic transformations and shifts of emphasis that have occurred, when Aristotle's concept of teleology and practical reason - within the work of Thomas Aquinas - encountered the specific philosophical demands and the different approach of Christian tradition. As a religion that is concerned with the view of eschatological anticipation and the experience of historical revelation, Christianity turned out to introduce a first perspective of "historical" thinking that was aimed to partly break down the more restricted ancient concept of ethics and politics. Being however constrained to a mere theological explanation, freedom of man is gaining a more universal and transcendent notion. The fulfilment of human nature is basically detached from its ancient close link to politics. But this development also changes the significance and the structures of the political and public sphere. It turns out to weaken and dilute the institutional achievements of the aristotelian republic. On the other hand the new resort to the universal demand of the transcendent "common good" as the ultimate goal of human life, rather than to the developed customs of the ancient city, also favours a process of accelerating and diversifying individual and social human goals and practices. And this development focuses the status of Aquinas' concept of the "Law" that however transcends a mere authoritarian or "material" notion of ethics and law. Furthermore it takes over the legitimising tasks of the ancient community of free and virtuous citizens in procuring a legitimate basis of politics. And this basis is now gaining a higher degree of "universality" with regard to its transcendental reason as well as its concern with the expansion of moral subjectivity, which finally leads up to the political demands of modern times.